Utilising knowledge of failure mechanisms and failure patterns for improved equipment reliability - Esterhuizen, Johannes Lodewicus August (Stellenbosch : Stellenbosch University, 2012)
Thesis (MEng) -- University of Stellenbosch, 1995.